The Influence of Product Quality, Promotion, and Store Atmosphere on Revisit Intention: Case Study on Kettlebean Sidoarjo Coffee Shop Customers - Wisnu Pradana; Noor Aziz; R Iqbal Robbie (Universitas Muhammadiyah Malang, 2022)
The purpose of this study was to determine the effect of quality products, promotion, and store atmosphere on revisit intentions. This type of research is explanatory research. The population used in this study was 100 respondents, the sample was taken as a whole because it amounts to 100. The type of research data used was quantitative data and the data source in the study was primary data. Research data collection through questionnaires. The method of data analysis in this research is scale range, and multiple linear regression analysis. The calculation of the range of the quality product scale shows high results, the promotion scale shows high results, the store atmosphere scale shows high results and the revisit intentions show high results. The results showed that quality products, promotion, store atmosphere have a significant direct effect on revisit intention. Meanwhile, the store atmosphere variable has the most dominant influence on revisit intention.